Endoscopic management of postsurgical complications after metabolic and bariatric surgery - Stier, Christine; Belle, Sebastian; Téoule, Patrick (Visceral medicine, 2025)
Background: Following metabolic and bariatric surgery (MBS), a wide range of symptoms may indicate postoperative complications, all of which can prompt endoscopic inspection and multidisciplinary management of potential complications. Therefore, an anatomical and technical understanding of the previous surgical procedure and its forms of reconstruction especially after MBS is crucial for the attending endoscopist to optimize endoluminal therapy. A selective literature review has been performed. This overview of endoscopic complication management aims to outline the available options after MBS. Summary: Postoperative complication rates vary widely depending on the antecedent procedure and have been reported to be relevant after specific procedures such as laparoscopic sleeve gastrectomy or Roux-en-Y gastric bypass in the context of MBS. There is a timeline of 30 days in the postoperative course that divides early from late complications. While anastomotic leaks or endoluminal bleeding are considered typical early complications, late complications include problems such as strictures and anastomotic ulcers. Management of complications in the immediate postoperative period (very early complications) may require a multidisciplinary approach to optimize the outcome of complication management, involving the surgeon, the endoscopist and the ward physician who manages the patient round-the-clock. This hand-in-hand approach enables the best possible treatment for the patient, with endoscopy playing a crucial role in solving endoluminal problems in a much less invasive way than repeated surgical intervention, thereby contributing significantly to an easier postoperative course. Key Messages: The surgical approach, in cooperation with endoluminal complication management, constitutes comprehensive visceral medicine, as endoscopy is the helping hand of surgery in the context of MBS.
Online veröffentlicht: 8. Mai 2025
Gesehen am 26.08.2025